Inherited hypoxia: A new challenge for reoligotrophicated lakes under global warming. Issue 12 (10th December 2014) - Jenny, Jean‐Philippe; Arnaud, Fabien; Alric, Benjamin; Dorioz, Jean‐Marcel; Sabatier, Pierre; Meybeck, Michel; Perga, Marie‐Elodie
Abstract The Anthropocene is characterized by a worldwide spread of hypoxia, among other manifestations, which threatens aquatic ecosystem functions, services, and biodiversity. The primary cause of hypoxia onset in recent decades is human‐triggered eutrophication. Global warming has also been demonstrated to contribute to the increase of hypoxic conditions. However, the precise role of both environmental forcings on hypoxia dynamics over the long term remains mainly unknown due to a lack of historical monitoring. In this study, we used an innovative paleolimnological approach on three large European lakes to quantify past hypoxia dynamics and to hierarchies the contributions of climate and nutrients. Even for lake ecosystems that have been well oxygenated over a millennia‐long period, and regardless of past climatic fluctuations, a shift to hypoxic conditions occurred in the 1950s in response to an unprecedented rise in total phosphorus concentrations above 10 ± 5 µg P L−1. Following this shift, hypoxia never disappeared despite the fact that environmental policies succeeded in drastically reducing lake phosphorus concentrations. During that period, decadal fluctuations in hypoxic volume were great, ranging between 0.5 and 8% of the total lake volumes. We demonstrate, through statistical modeling, that these fluctuations were essentially driven by climatic factors, such as river discharge and air temperature. In lakes Geneva and Bourget, which are fed by large river systems, fluctuations in hypoxic volume were negatively correlated with river discharge. In contrast, the expansion of hypoxia has been related only to warmer air temperatures at Annecy, which is fed by small river systems. Hence, we outline a theoretical framework assuming that restored lake ecosystems have inherited hypoxia from the eutrophication period and have shifted to a new stable state with new key controls of water and ecosystem quality. We suggest that controlling river discharge may be a complementary strategy for local management of lakes fed by large river systems.